NEW METHOD TO IMPROVE THE ADHESION STRENGTH OF TUNGSTEN THIN-FILM ON SILICON BY W2N GLUE LAYER - KIM, YT; LEE, CW; MIN, SK (AMER INST PHYSICS, 1992)
When the partial pressure ratio of WF6:NH3:H-2 is 2:1:50, (111) and (200) oriented tungsten nitride (W2N) thin films can be deposited by plasma enhanced chemical vapor deposition and the resistivity of as-deposited films is 95-100-mu-m cm. In order to improve the adhesion of chemical vapor deposited tungsten (W) thin films, this W2N glue layer is interposed between W and Si. The acoustic emission-load graphs obtained by the scratch test method show that the adhesion strengths of W films on the W2N glue layers are apparently improved from 1-2 to 9-11 N. The more adhesive contact can be attributed to the introduction of nitrogen interstitials because these nitrogen interstitials are expected to modify the structural properties such as porosity and vacancies in the W2N films.
Keywords: TITANIUM NITRIDE; DEPOSITION; BARRIER